Rancang Bangun Alat Penumbuk Adonan Guna Meningkatkan Efisiensi Produksi Dan Higienis Pada Produk Biskuit Dengan Pendekatan Ergonomi Dan Kelayakan Investasi - Armadani, Handhika Mahindra; Purnama, Jaka; Yuwono, Istantyo (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
UMKM Banjar Biscuit "Bu Min" in Sumber Nongko Village, Jombang Regency produces traditional snacks made from sticky rice using manual methods, especially at the dough-pounding stage. This manual process causes physical fatigue in workers, affects production efficiency, and threatens product hygiene. With increasing market demand, UMKM faces major challenges in meeting consumer needs. To overcome this problem, an ergonomic dough-pounding tool was designed with dimensions of 140 cm high, 50 cm wide, 50 cm long, and a mortar diameter of 30 cm. This tool successfully reduced the Work Heart Rate (WHR) of workers from 118-149 to 93-124 beats/minute, indicating a significant reduction in cardiovascular load. In addition to increasing production efficiency, this tool maintains product hygiene and reduces the risk of worker injury. From a financial perspective, the cost of making the tool of Rp 5,306,000 has proven to be economical with an IRR of 5.26% per month (51.2% per year), a Profitability Index of 6.04, a positive NPV, and a Payback Period of only 2 months. This innovation helps MSMEs improve the quality and quantity of production while strengthening competitiveness in a competitive market. Keywords: Anthropometry, Cardiovascular Load, Engineering Economics